Nucleolin-based targeting strategies for cancer therapy: from targeted drug delivery to cytotoxic ligands. Issue 10 (October 2019) - Romano, Sofia; Fonseca, Nuno; Simões, Sérgio; Gonçalves, João; Moreira, João Nuno
Highlights: Nucleolin is overexpressed at the surface cancer cells and tumor vasculature. Nucleolin enables dual cellular targeting strategies. Surface nucleolin as a target for intracellular drug delivery in solid tumors. Nucleolin-based targeting strategies have shown relevant anti-tumor effects. Nucleolin enables antibody-dependent immune responses. Abstract : Cancer is currently the second leading cause of death worldwide and current therapeutic approaches remain ineffective in several cases. Therefore, there is a need to develop more efficacious therapeutic agents, especially for subtypes of cancer lacking targeted therapies. Limited drug penetration into tumors impairs the efficacy of therapies targeting cancer cells. One of the strategies to overcome this problem is targeting the more accessible tumor vasculature via molecules such as nucleolin, which is expressed at the surface of cancer and angiogenic endothelial cells, thus enabling a dual cellular targeting strategy. In this review, we present and discuss nucleolin-based targeting strategies that have been developed for cancer therapy, with a special focus on recent antibody-based approaches. Teaser: Overexpression of nucleolin at the surface of cancer cells and endothelial cells of the tumor vasculature makes it a promising therapeutic target in solid tumors, having been the focus of different therapeutic strategies, including antibodies.